Faktor-Faktor yang Berhubungan dengan Pemeriksaan Kehamilan di Puskesmas Keramasan Palembang Tahun 2021 - Evi Holiday; Diah Sukarni; Rizki Amalia (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
According to WHO in 2017, MMR was still very high, around 810 women died from complications related to pregnancy or childbirth worldwide every day, and about 295,000 women died during and after pregnancy and childbirth. Efforts to accelerate the decline in MMR are carried out by ensuring that every mother is able to access quality maternal health services. The low number of pregnant women who do can be influenced by several factors. The factors that influence pregnant women to perform antenatal care are knowledge, attitudes, parity, economy, socio-culture, education and husband's support. The purpose of this study was to determine the relationship between knowledge, education and husband's support with antenatal care at the Keramasan Health Center Palembang in 2021. The research design used an Analytical Survey with a Cross Sectional approach. The population in this study were pregnant women in the third trimester (gestational age of more than 28-40 weeks) who came to check their pregnancy in August-September at the Keramasan Health Center Palembang, totaling 64 people. The sampling technique was accidental sampling with a sample size of 64 respondents. Collecting data using a questionnaire sheet. Data analysis used univariate analysis and bivariate analysis and chi square test. The results of the study showed that there was a relationship between knowledge, education and husband's support with pregnancy checks at the Keramasan Health Center Palembang in 2021. It is hoped that the results of this study can be an illustration for the Puskesmas to can further increase the visits of pregnant women in their working areas by providing information to pregnant women about the schedule and benefits of prenatal care.